Nutritional, Phytochemical, and Biological Activities of Chrysophyllum albidum Fruit Extracts from Lagos - Ngozi Awa Imaga; Franklyn Nonso Iheagwam; Edidiong Urua; Evarista Ayodele Ebigwai (The Scientific World Journal)
This study investigated the nutritional, phytochemical, and biological activities of Chrysophyllum albidum aqueous (CAA) and ethanolic (CAE) fruit extracts from Lagos. Proximate, vitamin and mineral compositions, phytochemicals, and antioxidant and antibacterial properties of the extracts were analysed. There was no difference in the composition of moisture content, total ash, carbohydrate, crude protein, fat, fibre, and caloric values in CAA and CAE. Elemental analysis showed the presence of sodium, iron, zinc, magnesium, calcium, manganese, potassium, and copper, while vitamins B1, B2, B3, B6, B12, C, D, and K were also present. The total tannin, flavonoid, and phenol contents of CAA were higher than those of CAE; however, CAE elicited stronger reducing power, antioxidant capacity, 2,2-diphenyl-1-picrylhydrazyl, and nitric oxide scavenging activities than CAA. The antibacterial activity of CAA was bactericidal on all tested bacterial clinical strains with the most promising activity against Pseudomonas aeruginosa. On the other hand, the antibacterial activity of CAE was bactericidal on all tested organisms except Staphylococcus aureus and Staphylococcus faecalis on which it was bacteriostatic. The most promising bactericidal activity was against Staphylococcus epidermidis and P. aeruginosa. These findings conclude the strong antioxidant effect of C. albidum fruit extracts in addition to a broad-spectrum antibacterial property.